Development of serious computer game based training module and its integration into working at heights mine site induction – paper II - Stothard, Phillip; van den Hengel, A. (AusIMM, 2010)
This paper reports the findings of a collaborative project that developed and demonstrated a serious computer game (SCG) based simulation training module for mine site inductions. It is the second of two papers. The project was collaboration between the University of New South Wales, the University of Adelaide, BHP Billiton Olympic Dam Expansion, Resources and Engineering Skills Alliance, Training and Further Education South Australia and SkillsDMC. The pilot project was aimed at improving mine site inductions by developing a prototype SCG for trainers to incorporate into their regular training activities. The outcome was a high quality generic SCG that provides an interactive visualisation of an Australian mine site operation under construction. The SCG was tested under controlled conditions and subsequently deployed on site.